2019
DOI: 10.4209/aaqr.2019.03.0127
|View full text |Cite
|
Sign up to set email alerts
|

Fine Particulate Matter-induced Toxic Effects in an Animal Model of Caenorhabditis elegans

Abstract: Research has been focused on the health hazards of ambient PM 2.5 related to humans. Many PM 2.5 toxicity assessments using in vitro studies have focused on PM 2.5 -bounded hazardous pollutants. However, PM 2.5 toxicity assessment by in vivo studies allow for better observation of the overall effects of PM 2.5 exposure on entire organisms, making in vivo PM 2.5 toxicity assessment relevant. The toxic effects of outdoor PM 2.5 , collected from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 55 publications
4
20
1
Order By: Relevance
“…Zhao et al, (2014) also found that TRAP PM 2.5 did not induce any adverse effects on the C. elegans after acute and prolonged exposure. One our previous report also showed no lethality for any ambient PM 2.5 sample collected from rural areas including NPUST (0.00144-1440 mg L -1 ) and Linluo Junior High School (0.00115-1150 mg L -1 ) (Chung et al, 2019). Further tests were made in order to confirm that PM 2.5 did not cause immediate mortality to the exposed nematodes.…”
Section: Lethal Effects Of Pm25 To C Elegansmentioning
confidence: 87%
See 2 more Smart Citations
“…Zhao et al, (2014) also found that TRAP PM 2.5 did not induce any adverse effects on the C. elegans after acute and prolonged exposure. One our previous report also showed no lethality for any ambient PM 2.5 sample collected from rural areas including NPUST (0.00144-1440 mg L -1 ) and Linluo Junior High School (0.00115-1150 mg L -1 ) (Chung et al, 2019). Further tests were made in order to confirm that PM 2.5 did not cause immediate mortality to the exposed nematodes.…”
Section: Lethal Effects Of Pm25 To C Elegansmentioning
confidence: 87%
“…Although this result is still unclear, further studies are necessary to identify the underlying mechanism. One our previous study also showed that high ambient PM 2.5 concentration had a negative effect on the brood size of the C. elegans (Chung et al, 2019). Moreover, several studies have demonstrated the dose-dependent manner reduction of the brood size of the nematodes exposed to different toxic compounds, such as PM 2.5 from coal combustion (Sun et al, 2015), cadmium (Wang et al, 2018), zearalenone (Yang et al, 2018), and silver nanomaterial (Moon et al, 2019).…”
Section: Effects Of Trap Pm25 On the Brood Size Of C Elegansmentioning
confidence: 87%
See 1 more Smart Citation
“…Caenorhabditis elegans (C. elegans), a nematode living in soil, has been established as an in vivo model for various applications such as in drug, nanomaterial, and chemical assessments in the biomedical field as well as for studying the toxicity of environmental contaminants such as metals, chemicals, fine particulate matter, and nanomaterials (Chung et al, 2019;Queiros et al, 2019). Its advantages over other in vivo models include a short life cycle and lifespan, easy maintenance, completely sequenced genome, large brood size, and a small, transparent body (Brenner, 1974;Shen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the combined application of different acellular methods on the same samples is strongly suggested. Although some recent studies were focused on the in vivo evaluation of PM's negative impacts on living organisms [18][19][20], knowledge about the relationships between OP and PM's toxicological effects still presents some important gaps [6,20,21].Other still unresolved issues are related to the assay's design and the influence of the operative conditions by which OP tests are performed. In fact, over recent years, many researchers underlined how test conditions could influence collected data.…”
mentioning
confidence: 99%